Tocilizumab improves the efficacy of anti-PD-1 in a patient with advanced gastroesophageal junction cancer: a case report - Cai, Yushi; Jin, Xuan; Dai, Yun (Frontiers in Oncology, 2025)
BackgroundCancer-related inflammation contributes to the progression of malignancies and considerably affects therapeutic outcomes. IL-6 acts as a main mediator of both local and systemic inflammatory responses. Although IL-6 therapies have been successful in the treatment of inflammatory conditions, there has been little experience in patients with cancer.Case presentationA 66-year-old man was diagnosed with gastroesophageal junction squamous cell carcinoma (stage IV) with liver metastasis. The patient presented with notable cancer-associated systemic inflammatory symptoms, and experienced disease progression after initial two cycles of anti-PD-1 combined with chemotherapy. After tocilizumab treatment, the symptoms improved rapidly. The patient showed favorable response to subsequent anti-PD-1 plus second-line chemotherapy, and survived without disease progression.ConclusionTargeting IL-6 holds promise for the management of cancer-associated inflammation and improvement of therapeutic outcomes.